The Clash of Sustainable Development Goals with the Reality in Egypt: The role of the media on the perception of clean energy implementation. - Ebrahim, Nourhan Salah Hamed (AUC Knowledge Fountain, 2024)
Media has promoted sustainable development goals as essential for a country's social, economic, environmental, and political development. However, the SDGs may collide with the reality and impede development due to certain circumstances and challenges that might hinder the country’s ability to achieve these goals the same way they planned for. Besides, such challenges are not being covered in the media agenda, addressed by the government, or even been tackled in previous research. Thus, this study aims to examine whether there is a conflict between the SDGs and the reality in Egypt, focusing on SDG 7 (Clean Energy) by analyzing the effects of SDG 7 new regulations on Egypt's industrial sector, economy, environment, and society. In addition to examining how the media placed this topic on top of its agenda and how its coverage has been reflected on the industrialists’ perception towards the clean energy implementations. This study was essential to expose the potential conflict between SDGs and the reality in Egypt and understand how such conflict could affect the industrial sector, the environment, the economy, and Egyptian society. Besides, the study will be a vital foundation for policymaking and implementation regarding clean energy (SDG 7) in Egypt. To achieve the aim of the study, four hypotheses, H1, H2, H3, and H4 were developed. H1 sought to unveil whether SDG 7 implementation challenges adversely affected Egypt’s industrial sector and economy. H2 examined whether clean energy regulations adversely affect Egypt’s economy, environment, and society. H3 assessed the extent to which industrialists are aware and ready to afford the costs involved in clean energy generation. Lastly, H4 examined the impact of the media coverage on the industrialists’ perceptions towards the clean energy sustainable development goal implementations. In addition, the topic of the current study is relatively new, and a survey would be able to capture the potential conflicts between the SDGs and the reality in Egypt, focusing on SDG no. 7 (Clean Energy) and help us understand its potential impact on the industrialist sector who are seeking to apply this goal and the role of the media in terms of its impact on the industrialists’ perception towards the SDG No. 7 and how its coverage has been reflected on the industrialists. Accordingly, the data for this study was collected from a sample of almost 500 industrialists from various industries in Egypt. This sample was divided into two groups: one for those who applied SDG7: clean energy (The engaged), and the other group for those who did not apply it before but applied other goals from the sustainable development goals (The disengaged). An argument has been revealed from the sample responses. The results showed that industrialists who applied SDG7: Clean Energy faced many obstacles and struggled with the high financial costs of turning from traditional to clean energy. Afterward, In-depth interviews were conducted with four clean energy consultants and experts. Their insights on the survey findings highly supported the thesis statement. On the contrary, those participants who had never applied SDG7: Clean energy in their industry before, praised the importance of applying clean energy to support the Egyptian economy and stressed that the implementation of this goal did not have any difficulties or problems and that its application would not only benefit the economy but also benefit society and the environment. Keywords: Media; SDGs-Sustainable Development Goals; Greenhouse Emissions; Egypt's Vision 2030; Economic growth; Climate Action; Climate Change; SCCP- Suez Canal Corridor Project; SDS- Sustainable Development Strategy; CBD-Convention on Biological Diversity; United Nations Development Program; DRM-Domestic Resource Mobilization.